(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
It is crucial to assess the financial performance of a company since finances are considered the lifeline of any company. The objectives of the study to analyses and compare the financial performance of Electric Vehicles (EVs) in Maruti Suzuki India Ltd and Honda Cars India Ltd. The importance of financial performance analysis to a company’s success is the main topic of this research. One purpose of financial statement analysis is to find correlations and trends in the data. An organization’s financial statements must be understood by both its internal management and those outside the company who use them (for example, creditors, investors, & analysts) such as revenue, profit margins, market share, investments, and future growth prospects in the EV segment. For the five-year period covering 2019–2020 to 2023–2024, the necessary data for the study was gathered from secondary sources, including company annual reports, journals, the internet, etc.